Mary Hays, an eighteenth-century woman lexicographer at the service of "the female world" - Lasa Álvarez, Begona (ELOPE (Ljubljana), 2018)
The English reformist writer Mary Hays published a compilation of women's biographies entitled Female Biography (1803), with the aim at providing other women with examples to emulate. She intended not only to convey her deepest convictions about women's capacities and abilities, but also to leave her own stylistic imprint on the text. This study seeks to analyse diverse entries of Hays's collection (Lady Dudleya North, Lady Damaris Masham, Margaret Roper, Aphra Behn, and Lady Rachel Russel) in order to elucidate her concerns as a data collector and biographer, and her techniques as a lexicographer, which are chiefly shaped by her concern about education and by her intended audience: women.
Keywords: 18.st.; angleške leksikografinje; biografije žensk; Hays, Mary; leksikografija; ženske biografije